PENGARUH PEMBERIAN PAKAN DENGAN KANDUNGAN L-LYSIN DAN DL-METHIONIN BERBEDA PADA ITIK BETINA TERHADAP JUMLAH LEUKOSIT DAN DIFERENSIAL LEUKOSIT - Semiyati, Semiyati; Santosa, Purnama Edy; Sutrisna, Rudy (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
The research aimed to determine the effect of: 1) the number of Leucocytes female ducks by L-Lysine and DL-Methionin at different levels; 2) the number of Leucocytes deferensial female ducks by L-Lysine and DL-Methionin at different levels. Examination of the number of Leucocytes and the differential leukocyte conducted in December 2016-January 2017 at the Laboratory Veteriner Region III Office of Bandar Lampung. This study using the completely randomized design (CRD) with 3 treatments and 4 replications. Number of female ducks used as many as 60 birds to 12 the number of plots cages so that each plot contained 5 female ducks. Data were collected at 10% of the number of ducks that exist in each treatment. The data were analyzed by analysis of variance on the real level of 5% or 1% and continued with Duncan test for the value of the variance analysis which showed significantly different results. Treatment of the ration given to the female duck has the content of L-Lysine and DL-Methionin are different so the best rations can be known towards the normal level of Leucocytes and differential leucocyte include lymphocytes, monocytes, heterophile, eosinophils. The result showed that giving rations with the levels of L-Lisyne and DL-Methionin different has not significantly effect (P>0,05) to the number of leucocytes and differential leucocyteKeywords: female ducks, Leucocytes, the differential Leucocytes, L-Lysine,DL-Methionin